Effect of apoptosis on gastric adenocarcinoma cell line SGC-7901 induced by cis-9, trans-11-conjugated linoleic acid - Liu, Jia-Ren (World J Gastroenterol, 2002)
AIM: To determine the effect of apoptosis on gastric cancer cells (SGC-7901) induced by cis-9, trans-11-conjugated linoleic acid (c9, t11-CLA) and its possible mechanism in the inhibition of cancer cells growth. METHODS: Using cell culture, flow cytometery and immunocytochemical techniques, we examined the cell growth, frequency of apoptosis and distribution of cell cycle, expression of ki67, bcl-2, Fas, and c-myc of SGC-7901 cells which were treated with various c9, t11-CLA concentrations (25, 50, 100 and 200 μmol·L(-1)) of c9, t11-CLA for 24 h and 48 h, with a negative control (0.1% ethanol). RESULTS: The growth of SGC-7901 cells was inhibited by c9,t11-CLA. Eight days after treatment with various concentrations of c9,t11-CLA, as mentioned above, the inhibition rates were 5.9%, 20.2%, 75.6% and 82.4%, respectively. The frequency of apoptosis on SGC-7901 cells induced by different concentrations of c9, t11-CLA (except for 25 μmol·L(-1), 24 h) was significantly greater than that in the negative control (P < 0.01). To further investigate the influence of the cell cycle progression, we found that apoptosis induced by c9, t11-CLA may be involved in blocking the cell cycle of SGC-7901 cells. Immunocytochemical staining demonstrated that SGC-7901 cells preincubated in media supplemented with different c9, t11-CLA concentrations for various time periods significantly decreased the expressions of ki67 (the expression rates were 18.70%-3.20%, at 24 h and 8.10%-0.20% at 48 h, respectively), bcl-2 (4.30%-0.15% at 24 h and 8.05%-0% at 48 h),and c-myc (4.85%-2.20% at 24 h and 4.75%-0.30% at 48 h) as compared with those in the controls (the expressions of ki67, bcl-2, and c-myc were 15.1% at 24 h and 13.5% at 48 h, 6.80% at 24 h and 8.00% at 48 h, 5.50% at 24 h and 5.30% at 48 h, respectively) (P < 0.01), whereas the expressions of Fas were increased (0.60%-2.75%, 24 h and 0.45%-5.95%, 48 h). CONCLUSION: The growth and proliferation of SGC-7901 cells are inhibited by c9, t11-CLA via blocking the cell cycle, pathways of bcl-2-associated mitochondria with reduced expression of bcl-2 and Fas-associated death domain protein (FADD) with enhanced expression of Fas. But expression of c-myc on SGC-7901 cells is lower than that in negative control, which needs to be studied further.